Chemical Modelling of the Neutralisation Process for Acid Uranium Mill Tailings - G. H. Khoe (The Minerals, Metals and Materials Society, 1991)
Neutralisation of acid uranium mill tailings with lime or other alkaline materials is usually practised to reduce the dissolved concentration of heavy metals and radio nuclides. Computer modelling of this process was carried out using the geochemical equilibrium code MINTEQA2. Computed dissolved metal and sulfate concentrations were compared with laboratory-based experimental data. It was found necessary to include the modelling of adsorption of trace metals (such as uranium and lead) by the precipitated ferric hydroxide in order to obtain acceptable concentrations in the neutralised liquors. There were limitations of the modelling exercise due to important aspects which were not addressed or properly accounted for such as chemical reaction kinetics and the effect of high ionic strength. These are discussed in the paper.